Hypoxia and activation of hypoxia inducible factor alpha as influencers of inflammatory helper T cells in autoimmune disease – a link between cancer and autoimmunity - Almanzar, Giovanni; Alarcon, Juan Carlos; Garzon, Ruth; Navarro, Ana Maria; Ondo-Méndez, Alejandro; Prelog, Martina (Frontiers in Immunology, 2025)
As a part of the tumor microenvironment, hypoxia is an important hallmark in the tumor progression. Hypoxia is a condition in which the oxygen supply is not sufficient to sustain the cell demand. In addition to its known impact in tumor progression, hypoxia seems to play a principal role in the generation and evolution of several autoimmune diseases. Both tumor and autoimmune diseases can be modulated by the hypoxia inducible factor alpha (HIF-1α) sharing similar molecular mechanisms. Here, we outline the links between cancer and autoimmunity regarding hypoxia-induced factors, such as HIF-1α, and describe the role of hypoxia in the modulation of the autoimmune response.